On Display: Miscellaneous Objects in Early Holocaust Exhibitions in Poland - Pietrasik, Agata (Holocaust and genocide studies, 2025)
In the immediate aftermath of the Second World War, the Central Historical Commission - and later the Jewish Historical Institute - in Warsaw organized pioneering exhibitions on the Holocaust. The most significant, "Martyrology and Struggle," took place at the Jewish Historical Institute in 1948. As one of the earliest public narratives of the genocide, this exhibition also marked initial efforts to present the Commission's diverse archival materials to a wider audience. Despite its significance, it received limited scholarly attention. This article argues that early exhibitions merit broader recognition and analysis. By examining how Holocaust-related objects and artifacts functioned within these displays, it explores the interplay between spatiality and narrativity. Employing the concept of "awkwardness," the author critically assesses exhibitions within their postwar contexts and the emerging museological discourses on representing genocide.